Evaluation of the spatial quality of the Largo São João of the Avaré Touristic Resort – SP - Massud, Nigme [UNESP]; Magagnin, Renata Cardoso [UNESP] (University Nove de Julho, 2024)
Squares play an important role in cities, as they are places for social interaction and contact with nature. They constitute an important space for cultural, social, and political expression. They represent the customs and culture of a society. Studies on the evaluation of public spaces show that different aspects can contribute positively or negatively to the vitality of these places. Objective: Assess the spatial quality of a public space and its immediate surroundings, considering different elements, which can positively or negatively impact the vitality of this place. Methodology: Based on a multi-method approach, whose instrument was developed by Silva (2020), the evaluation is composed of three stages: i) performance indicators and the Plaza Quality Index (acronym in Portuguese - IQEP), ii) topoceptive analysis; and iii) systematic observation using a behavioral map. Originality/Relevance: The use of complementary quantitative and qualitative techniques allows for a broader diagnosis of the public space, which supports the proposition of more assertive solutions to promote the vitality of this space. Results: The results show that the public space is favorable for people to use and stay there, however, it needs some improvements in relation to aspects involving user safety. And, the presence of leisure equipment, for different age groups, can give greater vitality to the space. Social / management contributions: Knowing the problems that negatively affect the use and vitality of a public space can support the proposal of design guidelines and activities to requalify this space.
Evaluación de la calidad espacial del Largo São João del Polo Turístico de Avaré - SP
Avaliação da qualidade espacial do Largo São João da Estância Turística de Avaré - SP
Keywords: Largo São João; spatial quality; square